Detection of markers predictive of macrolide and fluoroquinolone resistance in Mycoplasma genitalium from patients attending sexual health services. (4th June 2021) - Day, Michaela Joanne; Cole, Michelle Jayne; Fifer, Helen; Woodford, Neil; Pitt, Rachel
Abstract : Objectives: This study sought to provide data on the prevalence of macrolide (23S rRNA) and fluoroquinolone ( parC ) resistance-associated mutations seen in Mycoplasma genitalium -positive specimens received in the UK national reference laboratory. Methods: In total, 2580 clinical specimens from patients with suspected or confirmed M. genitalium infection were received at the national reference laboratory between September 2017 and November 2018. M. genitalium -positive clinical specimens were identified using a reverse transcription-PCR targeting two M. genitalium genes: MgPa and gap . Resistance-associated single nucleotide poylmorphisms were sought in all positive specimens by sequence analysis of the 23S rRNA and parC genes. Results: Eighteen per cent (458 of 2580) of clinical specimens were positive for M. genitalium and 389 had sequence data for both macrolide and fluoroquinolone resistance markers. Of these, 71% (275 of 389) had macrolide resistance-associated mutations, 8% (31 of 389) had fluoroquinolone resistance-associated mutations (S83I/R and D87Y/N) and 7% (26 of 389) had mutations associated with resistance to both antimicrobials. Only 28% (108 of 389) had no mutations associated with resistance to either class of antibiotic. Five specimens had mutations of unknown clinical significance in the parC gene (eg, G81C and S83N). Conclusions: Mutations associated with resistance to macrolides were very frequent. By contrast, susceptibility to the second-line treatment, moxifloxacin (a fluoroquinolone), was estimated at 92% based on the absence of resistance-associated mutations. The few specimens with mutations of unknown clinical significance in the parC gene were excluded from the analysis and so the actual level of fluoroquinolone susceptibility may be slightly lower than that reported here. Surveillance of antimicrobial resistance in M. genitalium is imperative for this to remain a treatable infection.